If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 157 = 113 + -1u Solving 157 = 113 + -1u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add 'u' to each side of the equation. 157 + u = 113 + -1u + u Combine like terms: -1u + u = 0 157 + u = 113 + 0 157 + u = 113 Add '-157' to each side of the equation. 157 + -157 + u = 113 + -157 Combine like terms: 157 + -157 = 0 0 + u = 113 + -157 u = 113 + -157 Combine like terms: 113 + -157 = -44 u = -44 Simplifying u = -44
| 2(x+19)=x+29 | | 4+4x=x | | -9t+-7(-6+-10)= | | 2(x+9)=x+29 | | y-47=-41 | | x-40=30 | | 22=9n-(-4) | | 6(n-4)=-54 | | 4(m-2)=1 | | 13=6+6 | | log[5]3+log[5]t+log[5](t+4)=log[5]63 | | -2(10x-1)=-48-10x | | 2(x+2)=3x-8 | | 16-7x=-61 | | 10m+9n+4m= | | -4+6(-6+10h)-4h= | | 1.8d+3=2(.9d-1.5) | | A(x)=2x+8x+14 | | 3m+7=7m+6 | | -12+5k=15-45 | | (9x-6)+(3x+8)= | | 7(2+9g)= | | 7.50x+4.75x=891.25 | | 6(3+5y)+(y-8)=13 | | f(x)=-5x+5 | | -10(-2s+1)+6= | | -3x-10=-9x-2 | | log[b](y-3)-log[b](y-4)=log[b](y+3)-log[b]y | | -8a+7(1+5a)=-17+3a | | -5+20x+5x+10=180 | | 5y-1=2y | | -x+3y=28 |